2014
DOI: 10.1007/s12012-014-9273-z
|View full text |Cite
|
Sign up to set email alerts
|

Modified High-Density Lipoproteins by Artificial Sweetener, Aspartame, and Saccharin, Showed Loss of Anti-atherosclerotic Activity and Toxicity in Zebrafish

Abstract: Safety concerns have been raised regarding the association of chronic consumption of artificial sweeteners (ASs) with metabolic disorders, especially in the heart and brain. There has been no information on the in vivo physiological effects of AS consumption in lipoprotein metabolism. High-dosage treatment (final 25, 50, and 100 mM) with AS (aspartame, acesulfame K, and saccharin) to human high-density lipoprotein (HDL) induced loss of antioxidant ability along with elevated atherogenic effects. Aspartame-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Zebrafish embryos were treated with water extract of PM 2.5 (final 3 and 30 ppm, wt/vol) according to our previous report ( Kim et al, 2015a ), based on the assumption that all components of PM 2.5 were completely dissolved in the aqueous medium. In a preliminary study, we found that a final concentration of 3 ppm of PM 2.5 was lethal to zebrafish after 10-fold serial dilutions from 0.0003 to 300 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish embryos were treated with water extract of PM 2.5 (final 3 and 30 ppm, wt/vol) according to our previous report ( Kim et al, 2015a ), based on the assumption that all components of PM 2.5 were completely dissolved in the aqueous medium. In a preliminary study, we found that a final concentration of 3 ppm of PM 2.5 was lethal to zebrafish after 10-fold serial dilutions from 0.0003 to 300 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Although ACE was proved safe for human use by the US Food and Drug Administration (FDA), the public protection agencies in the European Union and China, it was reported that ACE may cause DNA damage in the bone marrow cells of mice (Bandyopadhyay et al 2008) and interfere with photosynthesis in plants (Subedi and Kannan 2014). Increased reactive oxygen species (ROS) production in zebrafish embryo and a higher embryo death rate was found when the fish were exposed to low g/L dosage ACE (Kim et al 2015). Some other ASs would cause developmental toxicity to Oryzias latipes (Lee and Wang 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that high concentrations of aspartame and saccharin (25-100 mM) impaired the beneficial anti-atherogenic activities of HDL, induced embryonic toxicity and increased ROS production [30].…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerotic apolipoprotein E-deficient (apoE-/-) mice, consumption of aspartame-acesulfame K sweetened 'light' cola was found to accelerate the progression of atherosclerotic plaques and the accumulation of sub-endothelial lipid-laden macrophages [27,28]. Also, in vitro treatment of apoA-I or HDL with physiological concentrations of aspartame, acesulfame K, or saccharin resulted in their pro-oxidative and pro-atherogenic modifications [29,30]. On the other hand, consumption of stevioside by leptin and LDLR double knockout mice was reported to reduce the aortic plaque volume by decreasing the content of macrophages, lipids, and ox-LDL in the plaque [31].…”
Section: Introductionmentioning
confidence: 99%